The Russia-Ukraine crisis poses a serious food security threat for Egypt - Abay, Kibrom A.; Abdelfattah, Lina Alaaeldin; Breisinger, Clemens; Glauber, Joseph W.; Laborde Debucquet, David (International Food Policy Research Institute, 2023)
Russia’s invasion of Ukraine has imperiled global food security — creating suffering within Ukraine and displacing millions while disrupting agricultural production and trade from one of the world’s major exporting regions. The latter threatens to drive rising food prices still higher and create scarcity, especially for regions most dependent on exports from Russia and Ukraine — particularly the Middle East and North Africa. In this post, we consider the impacts of the war on the wheat market, focusing on Egypt. Wheat is a key food item for this country, representing between 35% and 39% of caloric intake per person in the past few years. Wheat imports usually account for about 62% of total wheat use in the country. We conclude by listing a number of key policy actions aimed at diversifying imports in the short term and helping Egypt’s agrifood system transformation become fairer and more resilient. The latter is an absolute necessity in the context of looming threats from climate change and water scarcity.